The impact of intangible assets on the value of FMCG companies worldwide - Kashkinbayev Azamat; Jaxybekova Galiya; Rustamov Bezhan; Zhaishylyk Nurdana (Journal of Innovation & Knowledge (JIK), 2023)
This article is devoted to evaluating the role of intangible assets in the process of increasing the value of a company. As a sample, we have chosen FMCG companies around the world. The research was done on 90 FMCG companies. The theoretical part presents the 'Value Creation Mixer' model that allows visual identification and determines the role of this type of asset in creating company value. This study reveals that the majority of FMCG companies are undervalued in terms of the value of intangible assets by comparing the market value of intangible assets with the fundamental and theoretical value. Our empirical findings support the positive impact of intangible assets on companies' value based on a dynamic panel approach. The policy implications suggest managers protect intangible assets intending to maximize the value of the fast-moving consumer goods companies.
Keywords: G19; 650; Evaluation of intangible assets; Influences of intangible assets; Intangible assets; The value of the company